Problems in metallurgical thermodynamics and kinetics - Upadhyaya, G. S.; Dube, R. K. (Oxford ; New York : Pergamon Press, 1977)
Problems in Metallurgical Thermodynamics and Kinetics provides an illustration of the calculations encountered in the study of metallurgical thermodynamics and kinetics, focusing on theoretical concepts and practical applications. The chapters of this book provide comprehensive account of the theories, including basic and applied numerical examples with solutions. Unsolved numerical examples drawn from a wide range of metallurgical processes are also provided at the end of each chapter. The topics discussed include the three laws of thermodynamics; Clausius-Clapeyron equation; fugacity, activi.
9.6 Rate of Heterogeneous ReactionsExercises; APPENDIX 1: SI UNITS; APPENDIX 2: CONSTANTS AND CONVERSION FACTORS; APPENDIX 3: MATHEMATICAL OPERATIONS; BIBLIOGRAPHY; ANSWERS TO THE EXERCISES; INDEX; OTHER TITLES IN THE SERIES.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Keywords: Chemistry, Metallurgic; Thermodynamics; Electronic books